Neurobehavioral Outcome after Early Childhood Head Injury - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2004)
Neurobehavioral function following traumatic brain injury (TBI) in a school-aged population, recovery over a period of 30 months post-injury, and predictors of outcome were studied in three groups of children treated at University of Melbourne, Royal Children's Hospital, Australia.